Murder or Not? Cold Temperature Makes Criminals Appear to Be Cold-Blooded and Warm Temperature to Be Hot-Headed - Gockel, Christine; Kolb, Peter M.; Werth, Lioba (PLOS ONE, 2014)
Temperature-related words such as cold-blooded and hot-headed can be used to describe criminal behavior. Words associated with coldness describe premeditated behavior and words associated with heat describe impulsive behavior. Building on recent research about the close interplay between physical and interpersonal coldness and warmth, we examined in a lab experiment how ambient temperature within a comfort zone influences judgments of criminals. Participants in rooms with low temperature regarded criminals to be more cold-blooded than participants in rooms with high temperature. Specifically, they were more likely to attribute premeditated crimes, ascribed crimes resulting in higher degrees of penalty, and attributed more murders to criminals. Likewise, participants in rooms with high temperature regarded criminals to be more hot-headed than participants in rooms with low temperature: They were more likely to attribute impulsive crimes. Results imply that cognitive representations of temperature are closely related to representations of criminal behavior and attributions of intent.